Composite collagen sponge for bone injury repair loaded with stem cells as well as preparation method and application of composite collagen sponge
By preparing a mixture of collagen sponge and hydroxyapatite and subjecting it to pressure-release and chemical cross-linking treatments, the problem of traditional bone repair materials being unable to effectively load stem cells was solved, achieving rapid and efficient repair of bone injuries.
Patent Information
- Application Number
- CN202411431254.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-07
AI Technical Summary
Traditional bone repair materials cannot effectively load stem cells, resulting in slow bone injury healing and increasing the financial burden on patients.
Composite collagen sponges were prepared by mixing collagen sponges with hydroxyapatite and using pressure relief and chemical cross-linking methods to enhance their pore structure and physical properties, thereby loading stem cells and accelerating bone healing.
The prepared composite collagen sponge can effectively load stem cells, rapidly and efficiently repair bone tissue, provide a good growth environment, and promote high-quality repair of bone tissue.
Smart Images

Figure CN119258273A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of biomaterials, and more specifically, relates to a composite collagen sponge for bone damage repair loaded with stem cells, and a preparation method and application thereof. Background Art
[0002] Bone repair has always been a key scientific issue in the field of tissue regeneration. Although there have been relatively clear reports on the relevant mechanisms of bone repair, the slow healing of bone injuries and residual gaps remain a difficult problem that needs to be solved urgently. Bone repair is a dynamic and complex process involving multiple coordinated effects. Traditional bone repair materials cannot provide a good growth environment for the effective load of stem cells, making it difficult to quickly repair bone tissue, thereby increasing the economic burden on patients.
[0003] Collagen is the most abundant structural protein in animals. It is widely present in tissues and organs such as skin, bones and Achilles tendon. It is also one of the main components of waste processed by agricultural and sideline industries such as aquaculture and animal husbandry (cattle Achilles tendon, fish skin, fish scales, pig skin, etc.). As a biological macromolecule, collagen has good biodegradability and biocompatibility, and has broad application prospects in the biomedical field.
[0004] At present, we have a relatively comprehensive understanding of bone injuries. Natural bone injury healing is a complex process involving bone formation, growth and remodeling for proper repair. Because autologous transplantation is suitable for injuries accompanied by significant bone loss under clinical conditions, natural or synthetic biomaterials are needed as alternative materials. Currently, tissue engineering has been developing scaffolds that enable cell adhesion and proliferation. Therefore, the preparation of such scaffold materials has become a current research hotspot. Summary of the invention
[0005] The purpose of the present invention is to provide a composite collagen sponge for bone injury repair loaded with stem cells, and a preparation method and application thereof. The method comprises mixing collagen with hydroxyapatite, combining a pressurization and pressure relief method to increase the pores of the collagen sponge, and a chemical cross-linking method to strengthen the physical properties of the collagen sponge, so that the prepared composite collagen sponge can well load stem cells, effectively accelerate bone healing, and provide high-quality repair of bone tissue.
[0006] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a composite collagen sponge for bone damage repair loaded with stem cells, the preparation method comprising:
[0007] (1) adding a collagen sponge to an organic solution, stirring to dissolve the collagen sponge, and obtaining a collagen solution; then dialyzing the collagen solution; and finally adding hydroxyapatite powder, mixing, and self-packing;
[0008] (2) subjecting the collagen solution after the self-assembly in step (1) to a pressurized pressure-releasing and pore-forming treatment, and then pre-freezing and freeze-drying the solution to obtain a composite collagen sponge; wherein the pressurized pressure-releasing and pore-forming treatment has a pressure strength of 1-3 MPa;
[0009] (3) The composite collagen sponge is subjected to chemical cross-linking treatment, and then washed and freeze-dried to obtain the composite collagen sponge for bone damage repair loaded with stem cells.
[0010] According to the present invention, preferably, in step (1), the collagen sponge is bovine Achilles tendon collagen sponge;
[0011] The organic solution is an aqueous solution of acetic acid;
[0012] The concentration of the acetic acid aqueous solution is 0.01-0.05 mol / L.
[0013] In the present invention, the collagen sponge can be collagen from various sources to obtain a composite collagen sponge adapted to different biological signs, preferably bovine Achilles tendon collagen sponge.
[0014] According to the present invention, preferably, in step (1), the dialysis is performed to a pH of 7.0-7.4;
[0015] The dialysate used was a phosphate buffer solution with a pH of 7.2-7.4.
[0016] According to the present invention, preferably, in step (1), the mass ratio of the hydroxyapatite powder to the collagen sponge is 1:(0.5-2).
[0017] According to the present invention, preferably, in step (1), the temperature of the self-contained device is 35-40° C. and the time is 4-8 hours.
[0018] In the present invention, the autonomous packaging in step (1) is carried out in a constant temperature incubator.
[0019] According to the present invention, preferably, in step (2), the pre-freezing temperature is -75 to -85°C and the time is 12-18 hours.
[0020] According to the present invention, preferably, in step (3), the crosslinking agent solution used for the chemical crosslinking treatment is prepared by a method comprising the following steps: adding 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide to an ethanol aqueous solution, stirring evenly, to obtain the crosslinking agent solution; the molar ratio of the 1-ethyl-(3-dimethylaminopropyl)carbodiimide to the N-hydroxysuccinimide is (1-2):1; the mass concentration of the ethanol aqueous solution is preferably 85-95%;
[0021] The temperature of the chemical cross-linking treatment is 20-30° C. and the time is 4-8 hours.
[0022] In the present invention, preferably, the chemical cross-linking treatment is: adding the composite collagen sponge into a cross-linking agent solution and soaking it at 20-30° C. for 4-8 hours.
[0023] The second aspect of the present invention provides a composite collagen sponge for bone damage repair and loading stem cells prepared by the above preparation method.
[0024] The third aspect of the present invention provides the use of the composite collagen sponge for bone damage repair loaded with stem cells in the preparation of a composite collagen sponge for bone damage repair loaded with stem cells.
[0025] In the present invention, the loaded stem cells are stem cells having good biocompatibility with the bones to be repaired, such as patient-derived mesenchymal stem cells.
[0026] The technical solution of the present invention has the following beneficial effects: the composite collagen sponge of the present invention can well load stem cells and quickly and efficiently repair bone tissue damage.
[0027] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The above and other objects, features and advantages of the present invention will become more apparent through a more detailed description of exemplary embodiments of the present invention in conjunction with the accompanying drawings, wherein like reference numerals generally represent like components throughout the exemplary embodiments of the present invention.
[0029] Figure 1a and Figure 1b The photographs respectively show the bending and curling of the collagen sponge according to Comparative Example 1 of the present invention.
[0030] Figure 1c and Figure 1d The photographs respectively show the bending and curling of the collagen sponge according to Comparative Example 2 of the present invention.
[0031] Figure 1e and Figure 1f The photographs respectively show the bending and curling of the collagen sponge according to Comparative Example 3 of the present invention.
[0032] Figure 1g and Figure 1h The photographs respectively show the bending and curling of the collagen sponge according to Example 1 of the present invention.
[0033] Figure 1i A transmission electron microscope image of the collagen sponge according to Comparative Example 1 of the present invention is shown.
[0034] Figure 1j A transmission electron microscopy image of the collagen sponge according to Comparative Example 2 of the present invention is shown.
[0035] Figure 1k A transmission electron microscope image of the collagen sponge according to Comparative Example 3 of the present invention is shown.
[0036] Figure 1l A transmission electron microscopy image of the collagen sponge according to Example 1 of the present invention is shown.
[0037] Figure 2a The results of CCK-8 cell activity detection of HUVEC human umbilical vein endothelial cells according to the present invention are shown; wherein COL represents comparative example 1, COLH represents comparative example 2, COLPHC represents embodiment 1, and Control represents control group; ODratio represents mean fluorescence intensity.
[0038] Figure 2b The figure shows the CCK-8 cell activity detection result of ADSC rat adipose mesenchymal stem cells according to the present invention; wherein COL represents comparative example 1, COLH represents comparative example 2, COLPHC represents embodiment 1, and Control represents control group; ODratio represents mean fluorescence intensity.
[0039] Figure 3a A 3D fluorescence scanning side view at 450 nm of the composite sponge loaded with stem cells according to Example 1 of the present invention is shown.
[0040] Figure 3b A 3D fluorescence scanning front view at 450 nm of the composite sponge loaded with stem cells according to Example 1 of the present invention is shown. DETAILED DESCRIPTION
[0041] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.
[0042] The present invention is further described below by examples:
[0043] The collagen sponge used in the following examples and comparative examples is bovine Achilles tendon collagen sponge.
[0044] Example 1
[0045] This embodiment provides a composite collagen sponge for bone damage repair loaded with stem cells, and the specific preparation method is as follows:
[0046] (1) adding a collagen sponge to an aqueous acetic acid solution with a concentration of 0.05 mol / L, stirring to dissolve the collagen sponge to obtain a collagen solution, and dialyzing the obtained collagen solution to a neutral pH of 7.4; adding nano-hydroxyapatite to the above collagen solution and mixing thoroughly, and then placing it in a constant temperature incubator at 37° C. and culturing it for 6 hours; wherein the mass ratio of the added hydroxyapatite to the collagen sponge is 1:1; and the dialysate used for dialysis is a phosphate buffer solution with a pH of 7.4;
[0047] (2) taking out the cultured collagen solution and performing a pressure-releasing and pore-forming treatment, placing the treated mixed solution in an acrylic mold after the pore-forming treatment, pre-freezing it in a refrigerator, and then freeze-drying it to obtain a composite collagen sponge; wherein the pressure strength of the pressure-releasing and pore-forming treatment is 1.5 MPa; the pre-freezing temperature is -80°C, the pre-freezing time is 12 hours; the freeze-drying temperature is -60°C, and the time is 48 hours;
[0048] (3) chemically cross-linking the composite collagen sponge obtained in step (2), adding 1-ethyl-(3-dimethylaminopropyl) carbodiimide and N-hydroxysuccinimide to an ethanol aqueous solution with a mass concentration of 90%, stirring evenly, adding the mixture to a container containing the composite collagen sponge, immersing the composite collagen sponge, soaking the sponge at a constant temperature of 25° C. for 6 hours, and then soaking the sponge in distilled water for multiple times to clean the sponge, and then freeze-drying it again to obtain the composite collagen sponge for bone injury repair loaded with stem cells; wherein the molar ratio of the 1-ethyl-(3-dimethylaminopropyl) carbodiimide to the N-hydroxysuccinimide is 2:1; the freeze-drying temperature is -60° C., and the time is 48 hours.
[0049] Comparative Example 1
[0050] This comparative example provides a composite collagen sponge, and the preparation method of this comparative example is as follows:
[0051] (1) adding a collagen sponge to an aqueous acetic acid solution with a concentration of 0.05 mol / L, stirring to dissolve the collagen sponge to obtain a collagen solution, and dialyzing the obtained collagen solution to a neutral pH of 7.4; then placing the solution in a constant temperature incubator at 37° C. and incubating it for 6 hours; wherein the dialysate used for the dialysis is a phosphate buffer solution with a pH of 7.4;
[0052] (2) taking out the cultured collagen solution, placing it in an acrylic mold, pre-freezing it in a refrigerator, and then freeze-drying it to obtain a composite collagen sponge; wherein the pre-freezing temperature is -80°C, the pre-freezing time is 12 hours; the freeze-drying temperature is -60°C, and the time is 48 hours.
[0053] Comparative Example 2
[0054] This comparative example provides a composite collagen sponge, and the preparation method of this comparative example is as follows:
[0055] (1) adding a collagen sponge to an aqueous acetic acid solution with a concentration of 0.05 mol / L, stirring to dissolve the collagen sponge to obtain a collagen solution, and dialyzing the obtained collagen solution to a neutral pH of 7.4; adding nano-hydroxyapatite to the above collagen solution and mixing thoroughly, and then placing it in a constant temperature incubator at 37° C. and culturing it for 6 hours; wherein the mass ratio of the added hydroxyapatite to the collagen sponge is 1:1; and the dialysate used for dialysis is a phosphate buffer solution with a pH of 7.4;
[0056] (2) taking out the cultured collagen solution, placing it in an acrylic mold, pre-freezing it in a refrigerator, and then freeze-drying it to obtain a composite collagen sponge; wherein the pre-freezing temperature is -80°C, the pre-freezing time is 12 hours; the freeze-drying temperature is -60°C, and the time is 48 hours.
[0057] Comparative Example 3
[0058] The present comparative example provides a composite collagen sponge. The preparation method of the present comparative example differs from that of Example 1 only in that: step (2) does not perform pressure relief and pore-forming treatment, that is, step (2) specifically comprises: taking out the cultured collagen solution, placing it in an acrylic mold, pre-freezing it in a refrigerator, and then freeze-drying it to obtain a composite collagen sponge; wherein the pre-freezing temperature is -80°C, and the pre-freezing time is 12 hours; and the freeze-drying temperature is -60°C, and the time is 48 hours.
[0059] Test Example 1
[0060] The morphology analysis experiment of the collagen sponges prepared in the above examples and comparative examples was carried out as follows:
[0061] (1) The prepared collagen sponge is subjected to mechanical activities of curling and bending to test the flexibility of the collagen sponge. Photos are taken of the sponge in the curled and bent states.
[0062] (2) Transmission electron microscope images: Transmission electron microscope images of the comparative example and the embodiment were taken separately.
[0063] like Figure 1a-1lAs shown, compared with Comparative Examples 2-3 and Example 1, the pore structure and pore size of Comparative Example 1 are the worst, and the material will be damaged to a certain extent under the action of bending and curling; Comparative Example 2 has a certain improvement in mechanical strength after adding hydroxyapatite, but the internal pores of the material are uneven; Comparative Example 3 also achieves the effect of improving mechanical strength by adding hydroxyapatite and chemical cross-linking treatment, and the pore structure of the material is strengthened, but the porosity and pore size are smaller than Example 1; Example 1 will not break or break under the conditions of bending and curling, and can restore the original morphology after stopping the application of force. In addition, the internal pore size of the material is improved and the pore structure is also stable.
[0064] Test Example 2
[0065] The collagen sponges prepared in the above examples and comparative examples were subjected to CCK-8 biological toxicity experiments, as follows:
[0066] (1) Inoculate the cell suspension in a 96-well plate (100 μL / well), with approximately 5,000 cells per well.
[0067] (2) The cells were cultured and given 100 μL of a 10% collagen sponge extract (the extract consisted of collagen sponge and cell culture medium) as the material test group. The group to which the corresponding amount (100 μL) of cell culture medium was added was used as the control group. The cells were cultured for an appropriate period of time, 24, 48, and 72 hours.
[0068] (3) After the specified incubation time, 10 μL of CCK-8 solution was added to each well. The wells with the corresponding amount of cell culture medium and CCK-8 solution but no cells were used as blank control groups.
[0069] (4) The cells were incubated in the cell culture incubator for 2 hours and then detected using an ELISA reader.
[0070] (5) Measure the absorbance at 450 nm using an enzyme-labeled instrument.
[0071] The cell culture medium used in the above experiment is a complete culture medium (90wt% DMEM high glucose culture medium + 10wt% fetal bovine serum).
[0072] like Figure 2a and Figure 2b As shown, the cell viability of HUVEC human umbilical vein endothelial cells and ADSC rat adipose mesenchymal stem cells was basically not significantly different from that of the control group within 24, 48, and 72 hours. This shows that the materials COL (Comparative Example 1), COLH (Comparative Example 2), and COLPHC (Example 1) are non-cytotoxic and have no harmful effects on the human body, and reflect the feasibility of the materials loaded with stem cells.
[0073] Test Example 3
[0074] This test example is an implementation method of composite collagen loaded stem cells, and the specific implementation method is as follows:
[0075] (1) The composite sponge prepared in Example 1 was immersed in an ethanol aqueous solution having a mass concentration of 75% for 6 hours.
[0076] (2) Take out the soaked sponge and drain the liquid in a sterile culture dish. Then add adipose mesenchymal cell suspension to the sponge until the sponge is fully expanded. Place the sponge in a 37°C cell culture incubator for 48 hours. The cell concentration of the suspension is 1*10 4 cells.
[0077] (3) The composite sponge loaded with stem cells was stained with Hoechst 33342 standard staining solution for 40 minutes, and then repeatedly rinsed three times with pH = 7.4 phosphate buffer to wash away excess staining solution on the sponge.
[0078] (4) Use laser confocal microscopy to perform 3D fluorescence multi-layer scanning at 450 nm on the stained composite sponge loaded with stem cells.
[0079] like Figure 3a and Figure 3b As shown, the pores of the composite sponge loaded with stem cells in Example 1 are uniformly loaded with adipose-derived mesenchymal stem cells, indicating that the material can load adipose-derived mesenchymal stem cells and the cells can survive therein for more than 48 hours.
[0080] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.
Claims
1. A method for preparing a composite collagen sponge for bone damage repair loaded with stem cells, characterized in that: The preparation method comprises: (1) adding a collagen sponge to an organic solution, stirring to dissolve the collagen sponge, and obtaining a collagen solution; then dialyzing the collagen solution; and finally adding hydroxyapatite powder, mixing, and self-packing; (2) subjecting the collagen solution after the self-assembly in step (1) to a pressurized pressure-releasing and pore-forming treatment, and then pre-freezing and freeze-drying the solution to obtain a composite collagen sponge; wherein the pressurized pressure-releasing and pore-forming treatment has a pressure strength of 1-3 MPa; (3) The composite collagen sponge is subjected to chemical cross-linking treatment, and then washed and freeze-dried to obtain the composite collagen sponge for bone damage repair loaded with stem cells.
2. The preparation method according to claim 1, wherein In step (1), the collagen sponge is bovine Achilles tendon collagen sponge; The organic solution is an aqueous solution of acetic acid; The concentration of the acetic acid aqueous solution is 0.01-0.05 mol / L.
3. The preparation method according to claim 1, wherein In step (1), the dialysis is performed until the pH value is 7.0-7.4; The dialysate used was a phosphate buffer solution with a pH of 7.2-7.
4.
4. The preparation method according to claim 1, wherein In step (1), the mass ratio of the hydroxyapatite powder to the collagen sponge is 1:(0.5-2).
5. The preparation method according to claim 1, wherein In step (1), the temperature of the self-assembly is 35-40°C and the time is 4-8h.
6. The preparation method according to claim 1, wherein In step (2), the pre-freezing temperature is -75 to -85°C and the pre-freezing time is 12 to 18 hours.
7. The preparation method according to claim 1, wherein In step (3), the crosslinking agent solution used for the chemical crosslinking treatment is prepared by a method comprising the following steps: adding 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide to an ethanol aqueous solution, stirring evenly, to obtain the crosslinking agent solution; the molar ratio of the 1-ethyl-(3-dimethylaminopropyl)carbodiimide to the N-hydroxysuccinimide is (1-2):1; the mass concentration of the ethanol aqueous solution is preferably 85-95%; The temperature of the chemical cross-linking treatment is 20-30° C. and the time is 4-8 hours.
8. A composite collagen sponge for bone damage repair loaded with stem cells prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the composite collagen sponge for bone damage repair loaded with stem cells according to claim 8 in the preparation of a composite collagen sponge for bone damage repair loaded with stem cells.